Analisis Pengaruh Penerbitan Obligasi Syariah (Sukuk) Terhadap Pertumbuhan Ekonomi di Indonesia pada Tahun 2018-2022 - Yunnasti Anikagustin; Ariyo Setiawan; Laela Halimatus Sadiyah; Agus Eko Sujianto (Universitas 45 Surabaya, 2023)
The purpose of this study is to determine the effect of issuing Islamic bonds on the rate of economic growth. This study uses a quantitative method using regression analysis and using secondary data. Samples were taken from 5 observations assisted by using the eviews 9 application. The data used is annual data from Sharia Bonds and Economic Growth Rates in 2018-2022. Based on the results of the research, it shows that the Development of Islamic Bonds has a negative and significant effect on the independent variable Economic Growth (GDP).